HUBUNGAN ANTARA SELF-REGULATED LEARNING, MOTIVASI, SELF-EFFICACY, DAN KECERDASAN EMOSIONAL DENGAN PRESTASI AKADEMIK MAHASISWA KEDOKTERAN - Ibnu Hajar Khan (2022)
Academic achievement is an important factor in the success of medical students in the future because academic achievement determines job opportunities for them. Academic achievement is influenced by various factors such as self-regulated learning (SRL), self-efficacy, motivation, and emotional intelligence. This study aims to determine whether there is a significant relationship between self-regulated learning, self-efficacy, motivation, and emotional intelligence with the academic achievement of medical students at the UPN Veteran Jakarta . This research is an analytic study with a cross sectional. The questionnaire was used to measure SRL, self-efficacy, motivation, and emotional intelligence of students, while to measure academic achievement using GPA. The samples obtained were 211 medical students. The sampling technique used is proportional stratified random sampling. This study used Pearson correlation and multiple linear regression. Correlation test results obtained p = 0.000 for SRL and GPA, self-efficacy and GPA p = 0.259, motivation and GPA p = 0.000, and emotional intelligence and GPA p = 0.887. Simultaneously, all independent variables have a significant effect with a value of 26.6% on the GPA. In conclusion, motivation and SRL have a significant relationship with GPA, while emotional intelligence and self-efficacy have no significant relationship with academic achievement. Simultaneously, all independent variables have a significant effect on academic achievement. Keywords: self-regulated learning, self-efficacy, motivation, emotional intelligence, and GPA.